Antigenic and anticorpal diagnosis of invasive aspergillosis and candidosis in immunocompromised host - Marco Machetti; Anna Marchese (Microbiologia Medica, 2009)
Invasive aspergillosis (IA) and candidemia are an increasing cause of morbidity and mortality in immunocompromised patients, but diagnostic procedures are often hampered by critical patients conditions. In recent years, non-culture methods have reached a standardization level suitable to be marketed and widely employed. A method for a panfungal antigenic diagnosis, is the detection in serum of (1→3)-ß-D-Glucan (BDG), a polisaccaridic component of fungal cell wall. Best results can be obtained in Aspergillus, Candida and Fusarium infections, while the test performs poorly with Cryptococcus and in zygomycosis. The use of this method are limited by the high costs and by the need of disposable materials certified as glucan-free, in order to avoid false positive results. Galactomannan (GM) antigen detection is a method for non-invasive diagnosis of IA. The assay, in latex agglutination (LA) and enzymeimmunoassay (EIA) format, detect GM in serum, whose presence correlates with IA. Sensitivity and specificity strongly fluctuate (50-100% and 81-98% respectively) depending on the time of sampling, the positivity cut-off employed, the concomitant administration of antifungal drugs and of some antibiotics. Nevertheless the method is a very useful and widely employed tool for the diagnosis of IA. For the diagnosis of candidemia, two Candida antigens may be detected in serum: the 56°C heat-labile antigen in LA format, and the mannan antigen, in LA and EIA format. Both the methods perform quite well, but sensitivities and specificities are not so good to allow a routinely and useful use in clinical practice.